2009
DOI: 10.1007/s10237-009-0175-0
|View full text |Cite
|
Sign up to set email alerts
|

Influence of power-law rheology on cell injury during microbubble flows

Abstract: The reopening of fluid-occluded pulmonary airways generates microbubble flows which impart complex hydrodynamic stresses to the epithelial cells lining airway walls. In this study we used boundary element solutions and finite element techniques to investigate how cell rheology influences the deformation and injury of cells during microbubble flows. An optimized Prony-Dirichlet series was used to model the cells' power-law rheology (PLR) and results were compared with a Maxwell fluid model. Results indicate tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 40 publications
(103 reference statements)
0
26
0
Order By: Relevance
“…5B, A549 cells exhibit a complex rheology where the storage modulus follows a weak power law function of frequency with a power law exponent, ␣. Previous computational studies (13) predict that increases in ␣ result in a more fluidlike cell, and that this fluidization results in less plasma membrane rupture during airway reopening. Consistent with these computational predictions, Yalcin et al (47) demonstrated that depolymerizating the actin cytoskeleton leads to a large increase in ␣ and lower cell necrosis during cyclic airway reopening.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5B, A549 cells exhibit a complex rheology where the storage modulus follows a weak power law function of frequency with a power law exponent, ␣. Previous computational studies (13) predict that increases in ␣ result in a more fluidlike cell, and that this fluidization results in less plasma membrane rupture during airway reopening. Consistent with these computational predictions, Yalcin et al (47) demonstrated that depolymerizating the actin cytoskeleton leads to a large increase in ␣ and lower cell necrosis during cyclic airway reopening.…”
Section: Discussionmentioning
confidence: 99%
“…Under these conditions, the closure and reopening of fluid-filled airways generates interfacial and microbubble flows that can significantly damage the lung epithelium. Specifically, several investigators have used computational (13,14,23,25,29) and in vitro experimental (3,30,47,48) techniques to demonstrate that this interfacial flow generates complex mechanical forces that cause cell necrosis/plasma membrane disruption and detachment of cells from their substrate. In addition, mechanical forces associate with atelectrauma can also activate inflammatory signaling pathways (27,28).…”
mentioning
confidence: 99%
“…In a separate study, these authors also demonstrated that changes in the cell's biophysical properties can be used to prevent cellular necrosis and detachment during microbubble flows [20]. In support of this concept, Dailey and Ghadiali [21,22] have recently used imaged-based computational techniques to investigate how changes in cellular mechanics and morphology may be used to prevent cell injury and deformation. Naire and Jensen [23] also used theoretical models to show that the elastic modulus of the epithelial layer plays a key role in deter mining cell deformation during microbubble flows.…”
Section: Introductionmentioning
confidence: 94%
“…Results showed that mechanical strain induces the upregulation of collagen III and IV, as well as MMP-2 and -9 expressions by lung fibroblasts, indicating a remodeling response of the tissue in vitro. Furthermore, studies have reported that the 3D computational models can be very useful in predicting cell-ligand or cell-cell interactions as well as in modeling mechanobiological responses such as epithelial layer disruption under the influence of hydraulic stresses generated by the movement of air-liquid interface or microbubble flow (36,87).…”
Section: Tissue-engineered Lung Models In Drug Development and Discoverymentioning
confidence: 99%